Mukjizat Rasulullah Berupa Al – Qur’an: Studi Ijaz Al – Qur’an - Dicky Syahfrizal; Airil Ihza Harefa; Husain Akbar; Aziz isroq (Jurnal Budi Pekerti Agama Islam, 2024)
The miracles of Prophet Muhammad SAW have distinct advantages compared to the miracles of other prophets. All previous miracles were limited in time and space, and were only shown to certain people at specific times. The miracle of the Qur’an is universal and eternal, applicable to all of humanity until the end of time. Therefore, the Qur’an is the greatest miracle of all the miracles that Allah SWT bestowed upon the previous prophets and upon Prophet Muhammad SAW himself. The miracle of Prophet Muhammad SAW manifests as a spiritual miracle that is rational, eternal, and everlasting. This is recorded in the Noble Qur’an as the greatest miracle performed by Prophet Muhammad SAW. Likewise, the miracles that were previously given to the prophets and messengers are no longer visible physically, except for the stories known as the Greatest Miracle of Prophet Muhammad SAW from the news of the Qur’an.